Contribution to the study of thyroid vascularization - Gary, Ruben; Ravera, Juan J; Azambuja, Néstor; Teliz, Norma; Acosta Ferreira, Walter (Cirugía del Uruguay, 2021)
The author stresses the importance of vascular factor in thyroid pathology, especially in the thyroid nodule. Includes a summary of ideas and main bibliographic contributions on the structure of the gland and its pattern of vascular distribution. This is followed by a study of vascularization aspects based on 30 anatomical specimens. Reference is made to displacements tow ards the large trunks, particulary to the position- of the subclavian artery and its main branches due to goites; the relation between the lower pole of the hypertrophic thyroid lobule and the vertebral artery -corroborated by clinical angiography data- show the frequency of displacement of its first segment. Morphological aspects of the pedicles are considered, especially the existence of vascular hilium in the superior lobe at the expense of a number of branches derived from the superior thyroid vein and artery which penetrate in the parenchima in a direct manner, in a well defined area. There is no homologous disposition with respect to the density of elements in the inferior pole. The characteristics of the superficial anastomotic network and of the intermediate or interlobe vessels. Are described and an analysis is made of the circulation characteristics of the thyroid nodule utilizing the documentation obtained in 8 specimens.